2008
DOI: 10.1111/j.1601-0825.2007.01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Microflora in oral ecosystems in subjects with radiation‐induced hyposalivation

Abstract: The microbial results explain why some RT subjects have an increased susceptibility to oral diseases and stress that site-specific microbial analysis is an important diagnostic tool when planning oral health preventive care for RT subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 29 publications
7
86
2
4
Order By: Relevance
“…In contrast, several studies have reported qualitative changes in oral flora during chemotherapy (23)(24)(25). Although such changes in oral flora are not well understood, the incidence of Candida species seems to increase after chemotherapy and radiotherapy for cancer (26), a trend also seen in oral flora obtained from immunocompromised hosts (27). In the present study, we found no significant differences in the prevalence of opportunistic microorganisms between the cancer treatment and control groups.…”
Section: Discussioncontrasting
confidence: 40%
“…In contrast, several studies have reported qualitative changes in oral flora during chemotherapy (23)(24)(25). Although such changes in oral flora are not well understood, the incidence of Candida species seems to increase after chemotherapy and radiotherapy for cancer (26), a trend also seen in oral flora obtained from immunocompromised hosts (27). In the present study, we found no significant differences in the prevalence of opportunistic microorganisms between the cancer treatment and control groups.…”
Section: Discussioncontrasting
confidence: 40%
“…This phenomenon is cumulative, usually established after 2000 cGy of radiation, accompanying the severity and persistence of xerostomia 17 . However, the use of sodium fluoride in aqueous solutions or gel minimizes the changes of cariogenic cocci populations, constituting a recognized strategy to prevent the rampant caries associated with RT and xerostomia [30][31][32] . Then, the elevations of cariogenic microorganisms in RT might be understood as result of the absence or precariousness of the preventive measures and the poor hygiene conditions of the patients and their deterioration along RT 33,34 .…”
Section: Radiation Caries Oral Streptococci and Mucositismentioning
confidence: 99%
“…Most of these pathogens are Gram-negative and with a wide spectrum of virulence, exacerbating the production and release of cytokines and chemokines 16 . Among Gram-negative bacteria, enteric rods of the family Enterobacteriaceae have been implicated in severe mucositis 20,21,50 and the oral carriage of these microorganisms is resilient to antimicrobials commonly used, what needs combined strategies involving improvement of oral hygiene to reduce the presence of enteric rods in the mouth of mucositis patients, particularly in patients presenting severe xerostomia 32,51 . Their presence on the surface of the oral soft tissues could exacerbate the microbial proteolytic activity on the fibronectin and connective tissues, intensifying the mucositis by the induction of inflammation by direct action of LPS and release of interleukins Il-1 and Il-6 23 .…”
Section: Mucositis Oral Bacterial Microbiota Enterobacteriaceae Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns estudos [18][19][20] e os resultados deste estudo indicam que a radioterapia aumenta bactérias entéricas e Candida durante o período imediatamente após a RT. Vários fatores podem contribuir para a colonização oral por estas espécies microbianas, tais como a hipossalivação induzida pela radiação, tabagismo, alcoolismo e presença de prótese [21].…”
Section: Materiais E Métodosunclassified